2000
DOI: 10.1007/pl00008460
|View full text |Cite
|
Sign up to set email alerts
|

α-Chemokine growth factors for adenocarcinomas; a synthetic peptide inhibitor for α-chemokines inhibits the growth of adenocarcinoma cell lines

Abstract: GROalpha and IL-8 are necessary for the growth of lung, stomach and colon adenocarcinomas, and can be inhibited by the hexapeptide, antileukinate. The findings suggest the possibility of using alpha-chemokine receptor inhibitors in the treatment of adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Recently, the current authors have shown that IL-8 is an important autocrine growth factor for A549 cells [34]. In addition, FUJISAWA et al [35] showed that the inhibition of IL-8 binding to tumour cells inhibited tumour growth of adenocarcinoma A549 in vivo. However, another study demonstrated that A549 cells did not proliferate in response to IL-8 [36].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, the current authors have shown that IL-8 is an important autocrine growth factor for A549 cells [34]. In addition, FUJISAWA et al [35] showed that the inhibition of IL-8 binding to tumour cells inhibited tumour growth of adenocarcinoma A549 in vivo. However, another study demonstrated that A549 cells did not proliferate in response to IL-8 [36].…”
Section: Discussionmentioning
confidence: 94%
“…Currently research mainly concentrated on the peptide bacterin, peptide antibiotics, antiviral peptides, cardiovascular active peptides, cytokine stimulating peptides, and anti-tumor peptides (Fujisawa et al 2000). We established a human hepatocarcinoma SMMC-7721 xenograft model in nude mice to verify antitumor eVects of YSV.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of IL-8 in tumor progression, metastasis, and angiogenesis has been demonstrated by several groups using neutralizing anti-IL-8 antibodies in the treatment of human adenocarcinomas transplanted into athymic nude mice (22,23,26). However, it is important to consider variation in the chemokine biology of rodents compared with humans, where mice express IL-8 receptors, but a murine analog of IL- 8 has not yet been identified.…”
Section: Fig 5 Il-8 Is a Potent Chemoattractant For Himec Migrationmentioning
confidence: 99%